Challenging Generations : Youths and Elders in Rural and Peri-Urban Sierra Leone - Manning, Ryann Elizabeth (World Bank, Washington, DC, 2014)
This paper takes a detailed look at the relationship today between elders and youths in rural and peri-urban Sierra Leone, and on how that relationship might have changed during and after the country's civil war of the 1990s. It focuses largely, though not exclusively, on political institutions. The main source of data is in-depth qualitative research conducted in 2006-2007 by the World Bank's justice for the poor and understanding processes of change in local governance project, though the paper also draws on other recent research efforts and select literature. The first section of the paper reviews the research methodology. The second section discusses different understandings of the term 'youth,' which sometimes cause confusion and contribute to misdirected policy efforts. The next sections review specific findings, followed by conclusions and recommendations for governmental and nongovernmental actors. The author hopes this information will be helpful to readers involved in efforts to empower youths or reform local governance and justice, as well as those interested more generally in avoiding the political and social conditions that helped drive the civil war.